2007
DOI: 10.1590/s1807-59322007000300013
|View full text |Cite
|
Sign up to set email alerts
|

Seating Position, Seat Belt Wearing, and the Consequences in Facial Fractures in Car Occupants

Abstract: . Seating position, seat belt wearing, and the consequences in facial fractures in car occupants. Clinics. 2007;62(3):289-94. INTRODUCTION:Trauma caused by traffic accidents is among the main etiologies involved in the occurrence of facial fractures throughout the world. However, the trauma mechanisms involved are different according to the location where the study was performed, due to different conditions of development, legislation, and culture. A retrospective study was done between February 2001 and July … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
7

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 7 publications
(11 reference statements)
2
9
0
7
Order By: Relevance
“…Results of a retrospective study of 323 individuals with facial fractures due to motorvehicle accidents at the São Paulo Clinics Hospital between February 2001 and July 2006 showed that the average age of the patients was 30.9 years and the proportion of men to women was 3.3 to 1 (see Table 1). 21 The findings are consistent with the results of a Minas Gerais study, which found that 23% of facial injuries were due to accidents involving bicycles and motorcycles, whereas 21% were due to interpersonal violence. In addition, trauma to the face from motorvehicle accidents was found to be more common among men (80%) than women (20%) 13.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Results of a retrospective study of 323 individuals with facial fractures due to motorvehicle accidents at the São Paulo Clinics Hospital between February 2001 and July 2006 showed that the average age of the patients was 30.9 years and the proportion of men to women was 3.3 to 1 (see Table 1). 21 The findings are consistent with the results of a Minas Gerais study, which found that 23% of facial injuries were due to accidents involving bicycles and motorcycles, whereas 21% were due to interpersonal violence. In addition, trauma to the face from motorvehicle accidents was found to be more common among men (80%) than women (20%) 13.…”
Section: Introductionsupporting
confidence: 90%
“…Despite all of the reported benefits, Pine et al42 revealed in 2009 that one‐quarter individuals in a university population were not using their seat belt. This is an alarming figure, considering that the age group most affected by deaths and facial injuries related to the use of seat belts is 20‐ to 40‐year‐olds 21,28. This has a significant impact on families and face traumas put these patients away from social interaction.…”
Section: Discussionmentioning
confidence: 99%
“…People using two wheelers for travelling are more prone to RTA than four wheeler users as two wheelers are relatively less stable and provide lesser protection to the riders, The most commonly involved mechanism of injury in current study was skid, followed by rear impact crashes. Protective effect of restraints offer a significant reduction in facial fractures in road traffic accidents [34,35]. Though legislation has made compulsory use of seatbelts and helmets in India, inspite of this the use of safety devices during driving is lacking, which is explained clearly by our figures in this study i.e.…”
Section: Two Wheeler As Most Common Vehiclementioning
confidence: 67%
“…Em um estudo recente, publicado por Fonseca et al (11) Mesmo após a obrigatoriedade do uso de cinto de segurança, estabelecido no código de trânsito brasileiro de 1997, acidentes automobilísticos continuam sendo as principais causas de fraturas faciais nos perímetros urbanos das metrópoles de nosso país (3) . Ressalta-se aqui a importância de uma educação no trânsito no sentido de se evitar dirigir sob efeito de bebidas alcoólicas e usar sempre o cinto de segurança, pois no caso em questão, se estas duas medidas tivessem sido seguidas, o paciente não teria perdido um olho.…”
Section: Discussionunclassified